PERANAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT TANI DI DESA BOYONG PANTE KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN - Ladua, Moh Fadli; Rompas, Sonny; Ruru, Joorie Marhaen (Sam Ratulangi University, 2016)
ABSTRACT: Indonesia is a country rich in natural resources, the natural resources that Indonesia has thecapital to promote development and the country's economy, but the extent to which it is known that theIndonesian people are less able to use these natural resources, especially people who lack the ability, as thereis in the countryside very need direction or assistance from the government in managing natural resourcesmore effectively. Based on the Human Rights Act Article 28c explains that every person has the right todevelop themselves through the fulfillment of basic needs, is entitled to education and to benefit from scienceand technology, arts and culture, in order to enhance the quality of life and for the welfare of mankind. Withthe role of government is being implemented in accordance with the rules villages minister in 2015 and otherlaws, to direct, inform and even provide facilities for the farming community or rather empowering thelivelihoods of the development will be better than ever. In the present study used qualitative data analysismethod. Informants in this study was taken from the village where the government carry out the role andrural communities where the feel of the role. From the research that has been conducted shows that thegovernment's role in empowering rural farming community in the village of Boyong Pante has not beenimplemented properly because of the lack of ability of village government in directing the villagers, as well asthe lack of compatibility between the villagers with the village government.Kaywords: village government, empowerment farmer